Variability of Agronomic and Metabolomic Characteristics of Nine Accessions of Cardamom (Amomum compactum) From Central Java, Indonesia - Haniefan, Nafarain Agung; Wiendi, Ni Made Armini; Santosa, Edi (Journal of Tropical Crop Science, 2025)
Amomum compactum (Javanese cardamom) is valued for its unique flavor and aroma, commonly used as a culinary spice or medicinal ingredient. The numerous accessions of cardamom in Indonesia present a significant potential for developing this spice. However, the specific potential of each accession remains to be discovered. This study records the variation of agronomical traits and metabolomic profiles of nine cardamom accessions from Central Java, Indonesia. Multivariate analysis using a heatmap on agronomical traits indicated significant variation among accessions, with clustering based on growth locations. Genetic parameter analysis revealed high phenotypic variability, but varying broad-sense heritability among traits, suggesting the influence of both genotypic and environmental factors. Metabolomic analysis using GC-MS reveals the presence of specific compounds in certain accessions, such as beta-panasinsene in the Kulonprogo Putih accession, 1-docosene and alpha-terpinene in the Banyumas Putih accession, and 9-tricosene in the Banyumas Hybrid, which can serve as markers for these accessions.